If it's not what You are looking for type in the equation solver your own equation and let us solve it.
m+7/3=-5
We move all terms to the left:
m+7/3-(-5)=0
We add all the numbers together, and all the variables
m+5+7/3=0
We multiply all the terms by the denominator
m*3+7+5*3=0
We add all the numbers together, and all the variables
m*3+22=0
Wy multiply elements
3m+22=0
We move all terms containing m to the left, all other terms to the right
3m=-22
m=-22/3
m=-7+1/3
| 3x+4=7x-66 | | 8x+0=3x+5 | | 3.2x-1=5 | | 1x+1.99=55.99 | | (2+3n)+4=-15 | | 3p+2=p+20 | | (11x)(-9x)=99x | | n-1/6=2 | | 2(x+5+3x)=8x+10 | | x(-7)=14 | | c+96=6c | | 3(x+5)=-4(x+2) | | -2(2x-4)=4x+6 | | x52+4=2 | | 23=6-n | | 5x=1=2x+19 | | x052+4=2 | | 6c=c+96 | | p^2-5=15 | | -1/2n+15=-9 | | 0.7x+5=0.2x+1 | | 85=6x+x+1 | | 12x-10+10x+8=360 | | 3-3.7b=20.3b-10 | | 3x-3+x-7=90 | | 4.5x−3=6 | | -10k+11=3+-2k | | 3x-8+x+14+90=180 | | 1/3(6+9n)+4=-15 | | 18-5x=78 | | 8(x-4)=2(x-1) | | m(-7)=35 |